Influence of single adsorbed atoms on charge exchange during ion-surface collisions - Romero, Marcelo Ariel (2023)
Partial and final projectile charge states are theoretically analyzed after Li+ ions frontally collide with a single-layer graphene surface with potassium atoms adsorbed on it, in the very low deposition limit where the adsorbed atoms negligibly interact with each other. We applied a model based on first principles that accounts for all the details of the surface and is used to describe the resonant charge exchange processes occurring in binary collisions between the projectile and the adsorbate, and between the projectile and the C atoms of the graphene surface located in the surroundings of the adsorption site. Completely different neutral fraction dependences with the outgoing velocity are found for the projectiles scattered by the adsorbate and by carbon atoms located far from the adsorbed atom. In addition, an important influence of the adsorbate is perceived in the neutralization of projectiles colliding with the first and second set of carbon atoms nearest to the adsorption site. For C atoms located at middle-range distances (∼6.7 Å), the final charge state of the projectile is not affected by the adsorbate presence, even when an effective interaction between the projectile and the K adsorbed atom is revealed via appreciable projectile level widths.